Epic Geography : James Joyce's Ulysses - Seidel, Michael, 1943- (Book collections on Project MUSE., 1976)
In proposing that places, movements, and directions are deeply implicated in the narrative structure of Ulysses, Michael Seidel contends that Joyce recreates in Dublin the significant epic geography of the Odyssey. The author demonstrates how Joyce adjusts the spaces of Ulysses to accommodate the three theaters of Homeric action as mapped by Victor Berard's Lex Pheniciens et I'Odyssee. Originally published in 1976. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.